Geochemical evidence for biogenic methane production and consumption in the shallow sediments of the SE Mediterranean shelf (Israel). (15th June 2015) - Sela-Adler, Michal; Herut, Barak; Bar-Or, Itay; Antler, Gilad; Eliani-Russak, Efrat; Levy, Elan; Makovsky, Yizhaq; Sivan, Orit
Abstract: This study presents geochemical evidence for biogenic methane formation (methanogenesis) in the shallow sediments of the oligotrophic SE Mediterranean continental shelf at water depths between 46 and 88 m. Depth-profiles of methane concentrations and related chemical parameters such as dissolved sulfate, dissolved inorganic carbon (DIC), and the stable carbon isotope composition of DIC and methane (δ 13 CDIC, δ 13 CCH4, respectively) were measured in six sediment cores (each 4.2–5.4 m long) in order to characterize the processes that involve methane production and decomposition. All the sediment cores reached the consumption depth of the entire sulfate pool and the in-situ microbial methane production (methanogenesis) zone. Methane concentrations reached saturation levels in one of the cores, but not in the others, probably because the zone of maximum methanogenesis was at a greater depth. Although the sediments exhibit a low TOC content of ~1%, the biogenic methane formation indicates a relatively high organic carbon lability capable of sustaining all redox microbial activity potential. Anaerobic oxidation of methane (AOM) was also evident in the sulfate–methane transition zone, showing a distinct isotope signature in diffusion limited conditions. Highlights: Methane was found in the shallow sediments of the oligotrophic SE Mediterranean continental shelf. Geochemical profiles suggest that the methane is of biogenic origin, produced in-situ in the shallow sediments. Anaerobic oxidation of methane (AOM) was also evident in the sulfate–methane transition zone. AOM shows isotope signature of diffusion limited conditions.